Sistem E-Point untuk Menunjang Surat Keterangan Pendamping Ijazah (SKPI) menggunakan Framework Yii2 - Regina Nila Sari; Vinno Christmantara; Michael Gerits Kriswanto Remetwa (Universitas Katolik Widya Karya Malang, 2023)
Certificate of Diploma Companion (SKPI) is not only considered as a complement but shows data on student activities and skills or skills both academic and non-academic that a student has. In making the SKPI document, it is also known that the student point system is used to calculate all of these activities and is used as one of the prerequisites for graduation. The problem the writer encountered was that publishing SKPI students took a long time and also with the large amount of student data managing the SKPI and not yet having an integrated e-point system, so in this study the authors carried out system development in calculating points to meet the website-based SKPI requirements using yii framework. Through the results of this study, the results of an e-point system were obtained which were able to streamline and speed up the calculation of points for SKPI